Judges, social rules and the Constitution: an empirical inquiry into the foundations of South African law - Friedman, N (2017)
This thesis examines whether HLA Hart’s theory of the nature of law has explanatory power for the South African legal system. The thesis discusses and elaborates on the empirical conditions necessary for the existence of the master rule of recognition that Hart posits as the foundation of every legal system properly so-called, and addresses certain difficulties associated with attempts to apply Hart’s theory to the concrete facts of any particular legal system. Drawing on a series of in-depth interviews with 12 past and present Justices of the Constitutional Court of South Africa, the thesis then explores whether the existence conditions for a Hartian rule of recognition can be observed in the practices and attitudes of the Justices, insofar as these relate to their judicial decision-making processes. The thesis concludes that many such existence conditions are absent from the Justices’ practices and attitudes: (i) the Justices do not appear to converge in their ultimate criteria of legal validity; (ii) the Justices do not perceive a common standard of judicial decision-making amongst their colleagues, but rather see fundamental differences; (iii) at least partly on account of their strong sense of judicial independence, the Justices are unconcerned with the kind of official criticism that is essential to motivate conformity to a Hartian rule of recognition; and (iv) the Justices celebrate, rather than condemn, decision-making processes that depart from their own. The thesis concludes that these findings provide strong prima facie evidence that Hart’s theory lacks explanatory power for the South African legal system. It also reflects on the implications of its findings for Hart’s theory more generally, and for the project of analytic legal philosophy as it is now conceived by its most prominent advocates.